Histamine enhances interleukin (IL)-1-induced IL-1 gene expression and protein synthesis via H2 receptors in peripheral blood mononuclear cells. Comparison with IL-1 receptor antagonist. - Vannier, E (1993)
Histamine and IL-1 have been implicated in the pathogenesis of chronic inflammatory diseases, such as pulmonary allergic reactions and rheumatoid arthritis. We therefore investigated whether histamine modulated the synthesis of IL-1 beta. Human PBMC were stimulated with IL-1 alpha (10 ng/ml) in the absence or presence of histamine (10(-9)-10(-4) M). Histamine alone did not induce protein synthesis or mRNA accumulation for IL-1 beta. IL-1 alpha-induced IL-1 beta synthesis was enhanced two to threefold by histamine concentrations from 10(-6)-10(-4) M. Cimetidine, an H2 receptor antagonist, reversed the histamine (10(-5) M)-mediated increase in IL-1 alpha-induced IL-1 beta synthesis. Diphenhydramine, an H1 receptor antagonist, had no effect. Indomethacin, a cyclooxygenase inhibitor, significantly reduced IL-1 alpha-induced IL-1 beta synthesis, but had no effect on the histamine-mediated increase in IL-1 alpha-induced IL-1 beta synthesis. Histamine (10(-5) M) enhanced and sustained IL-1 beta mRNA levels in IL-1 alpha-stimulated PBMC. However, histamine reduced IL-1 beta mRNA half-life (2.4 vs 1.2 h), suggesting that histamine enhances IL-1 alpha-induced IL-1 beta synthesis at the level of transcriptional activation. On the other hand, histamine (10(-5) M) did not affect IL-1 alpha-induced synthesis of IL-1 receptor antagonist. These results suggest that mast cells may sustain chronic inflammatory processes by upregulating self-induction of IL-1 through histamine release.